KONTRIBUSI ADVERSITY QUOTIENT DENGAN PROKRASTINASI AKADEMIK PADA MAHASISWA UNIVERSITAS NEGERI PADANG YANG SEDANG MENGERJAKAN SKRIPSI - Diflatul Amini (CV. ADIBA ASIHA AMIRA, 2024)
One of the obligations of students is to complete a thesis as one of the requirements for obtaining a bachelor's degree. The reality that occurs in the field is that there are still many UNP students who are still struggling to complete their thesis according to the applicable regulations. This procrastination in the academic realm is often called academic procrastination and is supported by many factors. There are many challenges that need to be overcome and an individual's ability to face obstacles and turn them into opportunities is called the adversity quotient. This research aims to see the contribution of the adversity quotient to academic procrastination in UNP students who are working on their thesis. This research uses quantitative research methods with a correlational descriptive approach. The subjects were 345 people (according to Isaac and Michael) who were taken using a cluster sampling technique from students from the Department of Psychology, Mathematics Education, Physics, Chemistry, Mining Engineering, Civil Engineering, Mechanical Engineering and Information Engineering Education. The data collection technique uses research scales, namely the academic procrastination scale and the adversity quotient scale, then analyzed using simple regression analysis techniques. Based on the results of the hypothesis test, a significance value of 0.000 <0.05 was obtained with an R Square value of 0.092. It can be interpreted that there is an adversity quotient contribution to academic procrastination among UNP students who are working on their thesis with a contribution to academic procrastination of 9.2%.